Evaluation of the Social Media Marketing Strategies of Tinybop Inc. In Bahay Toro, Quezon City: Basis for Customer Decision-Making Model: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The way business owners interact with their customers has changed as a result of globaltechnological advancement. Businesses currently use various marketing strategies, such associal media, to get customers' attention, interest, desire, and action. (Hassan et al. 2018).Tinybop Inc. is a business in Bahay Toro, Quezon City that sells baby garments. They areusing social media as their marketing strategy in order to gain sales, and most of theirinquiries and transactions are conducted online. However, there are instances that theirexisting social media marketing strategies are not enough to attract new customers andconvince their existing customers to repurchase.The findings of the study revealed that there is a very positive correlation between theassessment of social media marketing strategies and customer decision-making. Thefindings also revealed the assessment of social media marketing strategies of Tinybop Inc.in terms of representation, engagement, and listening-in and assessment of customerdecision-making in terms of awareness, research, consideration, conversion, andrepurchase.This study recommends that Tinybop Inc. should provide a budget for their social mediamarketing. Hire experienced social media managers and get more influencers to promoteand boost their products online. Also, Tinybop Inc. must be updated to the latest trends tomaintain customer retention.
Keywords: Business Administration